The synchronization of mathematical thinking and creativity in the performing art of Mak Yong / Wan Norliza Binti Wan Bakar … [et al.] - Wan Bakar, Wan Norliza; Mohamed Yusoff Fauzi, Fatimah Zuhaira; Shamsuddin, Rozita; Raja Yusof, Raja Norazila (2016)
Mak Yong is a performing art state somewhere in 1920's in few places of Terengganu, Pattani, Kelantan, Kedah, Perlis and Riau Islands. The objectives of the research are to study the elements in the performing art of Mak Yong, the evolution of ideas involved and the stimulation of mathematical thoughts and creativity in Mak Yong. The research method utilized in the study was the triangulation method consisting of observation, interview and analysis. In studying the elements of Mak Yong and evolution of idea in Mak Yong, we placed an interview with three mak yong experts. Moreover, the study on the stimulation of mathematical thinking and creativity were done through making an observation on video presentations as to analyze on which part the mathematical thinking and creativity happens. The findings revealed that the elements of Mak Yong are the combination of songs, dance,,romance and comedy which is done in a single presentation. The evolution of idea take place in the techniques of dancing,singing and drama. The stimulation of mathematical thinking happens in three aspects that are reasoning process, pattern recognition and the counting process in the dancing session. The creativity could be traced in the increasing techniques of dancing and storytelling. It is suggested that further extensive research can be conducted on the evolution of design in Mak Yong's dancers costume.